Prevalence and associated factors of uncontrolled blood pressure among hypertensive patients in a rural population of Salem, Tamil Nadu - Shankar Radhakrishnan; B Sanjana Arunthathi; S Arulprakash; S Sangeetha (Journal of Family Medicine and Primary Care)
Introduction: Hypertension, a significant risk factor for cardiovascular diseases, is a prevalent public health concern globally. It imposes a substantial burden on healthcare systems, particularly in low and middle-income countries like India. Despite the availability of effective treatments, hypertension remains poorly controlled leading to increased morbidity and mortality. Rural areas often face unique challenges in managing hypertension due to limited healthcare access and awareness. Objectives: The study aimed to estimate the prevalence of uncontrolled hypertension and to identify associated factors among hypertensive patients in rural Salem. Materials and Methods: A hospital-based cross-sectional study was conducted at the Rural Health Training Centre over six months. A total of 382 hypertensive adults aged 18 years and above were included. Data on sociodemographic characteristics, lifestyle factors and clinical profiles were collected using a pretested semistructured questionnaire. Clinical measurements included blood pressure, BMI, and laboratory investigations. Statistical analysis included Chi-square tests and logistic regression to determine factors associated with uncontrolled hypertension. Results: The study revealed a high prevalence of uncontrolled hypertension (62%) among rural hypertensive patients. Factors significantly associated with uncontrolled hypertension included older age (>60 years) (odds ratio [OR] = 2.3, P = 0.027), obesity (OR = 2.7, P = 0.001), employment (OR = 1.5, P = 0.048), diabetes (OR = 2.6, P = 0.036), alcohol consumption (OR = 2.8, P < 0.001), and lack of physical activity (OR = 3.2, P = 0.034). Compliance to treatment was associated with better blood pressure control (P = 0.002) with noncompliant patients having 1.23 times higher odds of uncontrolled hypertension. Conclusion: The study emphasizes the urgent need for tailored interventions addressing lifestyle modifications, patient education, adherence to treatment regimens, and improved healthcare access to enhance hypertension management. These efforts are crucial for reducing the burden of cardiovascular diseases and improving public health outcomes in rural communities.